Assessment of using state of the art unmanned ground vehicles for operations on peat fields - Riho Kägo; Priit Vellak; Edgar Karofeld; Mart Noorma; Jüri Olt (Mires and Peat, 2021)
In this article a concept is presented for replacing the tractors that haul machinery during necessary operations on peat fields with centrally controlled unmanned ground vehicles (UGVs). The objective is to reduce operational costs in terms of human labour, fuel consumption and the associated CO2 emissions. A robotic system architecture for the example of milled peat extraction has been developed and assessed on the basis of comparative analysis. Depending on the area of the extraction surface, the number of UGVs and the method of extraction, the fuel consumption and labour requirement for one season were determined using a combination of data from production records compiled by peat companies and field measurements using the UGV under assessment. It is demonstrated that utilising currently available robotic technology for milled peat extraction by either the Haku method or the ‘vacuum harvester’ method can reduce production-related labour requirement by 34–43 % and fuel consumption by 21–26 % with a corresponding reduction of CO2 emissions. Future advances in UGV technology will increase the advantages of robotic technology by reducing the requirements for human intervention as well as by using green energy in fully electric UGVs.